1998
DOI: 10.1007/s002130050498
|View full text |Cite
|
Sign up to set email alerts
|

Reinstatement of alcohol-seeking by priming injections of alcohol and exposure to stress in rats

Abstract: Previous studies using a reinstatement procedure have found that acute reexposure to the self-administered drug and exposure to footshock stress reinstate heroin and cocaine seeking after prolonged drug-free periods. Here we tested whether these findings generalize to alcohol-taking behavior. Male rats were initially allowed to consume alcohol in a two-bottle choice procedure (water versus alcohol) for 30 min/day for 36 days. Rats were then trained for 60 min/day in operant chambers to press a lever for the dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
126
2
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(138 citation statements)
references
References 40 publications
8
126
2
2
Order By: Relevance
“…The doses used in the reinstatement experiments were based on STUDY 1. As in our previous report (Lê et al 1998), footshock was found to be more effective than alcohol priming in reinstating drug seeking. The reasons for the potent effect of the footshock stressor on reinstatement of alcohol seeking as compared to alcohol priming are not known.…”
Section: For Reviews)supporting
confidence: 83%
See 1 more Smart Citation
“…The doses used in the reinstatement experiments were based on STUDY 1. As in our previous report (Lê et al 1998), footshock was found to be more effective than alcohol priming in reinstating drug seeking. The reasons for the potent effect of the footshock stressor on reinstatement of alcohol seeking as compared to alcohol priming are not known.…”
Section: For Reviews)supporting
confidence: 83%
“…In the present study, therefore, we used a reinstatement procedure, an animal model of relapse (Carroll and Comer 1996;Stewart and de Wit 1987), to study the effect of fluoxetine and naltrexone on relapse to drug seeking induced by reexposure to alcohol and exposure to a footshock stressor. Acute reexposure to alcohol (Bigelow et al 1977;de Wit 1996;de Wit and Chutuape 1993;Hodgson et al 1979;Ludwig et al 1974) and exposure to stress (Brown et al 1995;Cooper et al 1992;Hore 1971) are regarded as two important factors for provoking relapse in humans.We have recently modified the reinstatement method, previously used to study factors involved in relapse to opioid and stimulant drugs in rats and monkeys, in order to determine factors involved in relapse to alcohol seeking in rats (Lê et al 1998). We found that priming injections of alcohol produce a modest dose-dependent reinstatement of drug seeking, whereas footshock stress potently reinstates extinguished alcohol seeking.…”
mentioning
confidence: 99%
“…In this respect, anxiety during sobriety is reportedly a predictor of end-state drinking and return to alcohol abuse (Sloan et al, 2003;Willinger et al, 2002). The ability of stress to increase alcohol seeking in animals (Lê et al, 1998;Liu and Weiss, 2003; see a review by Lê and Shaham, 2002) is consistent with stress-enhancing craving during abstinence and increasing the probability of relapse and furthering alcohol abuse. The present protocol demonstrating a role for the adaptation induced by previous ethanol exposure in the stress-induced anxiety during abstinence provides a means to explore further the contribution of stress to the continuing abuse of alcohol.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, we do not know whether the small oral priming dose of ethanol alone could have reinstated responding, or whether the environmental cues associated with ethanol availability and the orosensory properties of ethanol acted additively to induce reinstatement. In this context, it is worth noting that although contingent or injected ethanol have been previously reported to reinstate ethanol responding, this effect shows high variability and inconsistency (Chiamulera et al, 1995;Lê et al, 1998Lê et al, , 1999Vosler et al, 2001;Lê and Shaham, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…In the reinstatement paradigm, the animal is trained under operant conditions to self-administer ethanol and is then subjected to extinction. Following extinction, various conditions have been reported to lead to reinstatement of ethanol seeking, including ethanol priming and stress (Lê et al, 1998). However, the most reliable reinstatement of ethanol seeking has been obtained after presenting the subjects with stimuli previously associated with ethanol availability (Katner et al, 1999;Ciccocioppo et al, 2001;Liu and Weiss, 2002).…”
Section: Introductionmentioning
confidence: 99%